(untitled) (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.1.5929.5-18. Presents the performance informations of Management and Connections Journal (Revista Gestão & Conexões) in its first year of operation (2012).